LEGAL ASPECTS OF PRACTICE AGREEMENT FISHING VESSEL FOR FISHERY PRODUCTS IN PEKALONGAN - Isti sulistyorini (LPPM Universitas Pekalongan, 2013)
This study aims to mngetahui legal aspects of the practice of fishery agreements for fishing boats in Pekalongan. This study uses a socio-juridical approach (non dokrinal) or empirical (socio legal research), the research took place in the area of Pekalongan. Data was collected through field studies and literature in order to obtain primary data and secondary data. Analysis of the data used is qualitative analysis. After the analysis we concluded that the implementation of the agreement for fisheries fishing vessels conducted orally with the principle of kinship and trust with the presentation in the distribution system as a result of the arrest results in sales. Issues arising in relation to socio-economic development of the communities and natural factors, thus affecting the incomeoffishermen. Keywords: practice, agreement for fishery products, fishing boat.